2013
DOI: 10.1111/jce.12322
|View full text |Cite
|
Sign up to set email alerts
|

Fusion‐Optimized Intervals (FOI): A New Method to Achieve the Narrowest QRS for Optimization of the AV and VV Intervals in Patients Undergoing Cardiac Resynchronization Therapy

Abstract: The FOI method is feasible, further reduces QRS duration, and improves acute hemodynamic response compared to nominal programming of CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 52 publications
2
61
0
Order By: Relevance
“…They found that optimal ventricular resynchronization was reached when BiVp fused with intrinsic conduction. These findings confirm similar observations in other studies …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…They found that optimal ventricular resynchronization was reached when BiVp fused with intrinsic conduction. These findings confirm similar observations in other studies …”
Section: Discussionsupporting
confidence: 94%
“…These findings confirm similar observations in other studies. 12,13,29 In our study, triple wavefront fusion was present during the settings associated with the best hemodynamic improvement by CRT in the vast majority of patients. The optimal moment for RVp in our cohort was around the onset of the intrinsic farfield signal (at 98 ± 17%% of RA-RV farfield ) while preactivating the LV at 50% of the RA-RV sense interval.…”
Section: Triple Wavefront Fusion In Crtsupporting
confidence: 49%
“…Several studies have confirmed this assumption and reported that decrease in QRSd during CRT was a predictor of acute and chronic hemodynamic responses to CRT. Moreover, adjusting the RV, LV pacing site, or AV delay individually to reduce QRSd was also associated with an improvement in the impact of CRT . However, contradictory results have also been published.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adjusting the RV, LV pacing site, or AV delay individually to reduce QRSd was also associated with an improvement in the impact of CRT. 16,[18][19][20][21] However, contradictory results have also been published. Recently, Gold et al have analyzed the changes in QRSd during BiV pacing in the REVERSE trial involving 610 patients.…”
Section: Relationship Between Pacing Induced Qrsd Changes and Hemodynmentioning
confidence: 99%
“…Additionally, although QRS intervals were similar at baseline, MG had a significantly shorter QRS interval than controls at the 6-month follow-up, which is comparable with better cardiac synchrony in MG. A longer Q-LV interval and a shorter QRS interval have been reported to be a better prognostic parameter of CRT response. [16][17][18][19][20] Thus, the Q-LV interval in MG versus CG represents a better prognosis of the former in this study. In the SMART-AV study, Gold et al found that patients with a Q-LV greater than the median 95 milliseconds had better outcomes.…”
Section: Discussionmentioning
confidence: 58%